2004
DOI: 10.3346/jkms.2004.19.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Animal Experimental Model for a Bileaflet Mechanical Heart Valve Prosthesis

Abstract: The objective of this study was to develop a pre-clinical large animal model for the in vivo hemodynamic testing of prosthetic valves in the aortic position without the need for cardiopulmonary bypass. Ten male pigs were used. A composite valved conduit was constructed in the operating room by implanting a prosthetic valve between two separate pieces of vascular conduits, which bypassed the ascending aorta to the descending aorta. Prior to applying a side-biting clamp to the ascending aorta for proximal grafti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Studies involving an ovine model for prosthetic mitral valve implantation have reported low mortality with acceptable physiological and hemodynamic data [5,6] . However, the use of adult sheep for prosthetic aortic valve implants has produced mixed success due to potential problems such as a limited anatomical length of the ascending aorta in cloven-footed animals [4] . Preoperative echocardiographic assessment can provide an estimated length of the ascending aorta [7] , which is useful information during candidate selection.…”
Section: Discussionmentioning
confidence: 99%
“…Studies involving an ovine model for prosthetic mitral valve implantation have reported low mortality with acceptable physiological and hemodynamic data [5,6] . However, the use of adult sheep for prosthetic aortic valve implants has produced mixed success due to potential problems such as a limited anatomical length of the ascending aorta in cloven-footed animals [4] . Preoperative echocardiographic assessment can provide an estimated length of the ascending aorta [7] , which is useful information during candidate selection.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike in the human patient, where the valve is chosen based on the patient's annular size and geometry, in preclinical research a suitable animal is generally selected based on body weight for one particular valve size available for testing. Thus, the suitable animal must be large enough to accommodate human-grade devices, with the determining factors being the size of the target cardiac structure, as well as the diameter of the peripheral vessels used for vascular access 17 .…”
mentioning
confidence: 99%